2017
DOI: 10.1097/iop.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgery in External Dacryocystorhinostomy

Abstract: Piezourgery is a viable modality for performing external DCRs. The lack of surgical complications shows a potential for decreased soft tissues damage. The surgical success rate based on patient-reported epiphora is similar to those published for mechanical external DCRs. This modality may benefit the novice surgeon in the reduction of soft and mucosal tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…This finding validates earlier research from Czyz et al, who suggested anecdotal improvements in operative time when using a piezosurgical device. 6 One key difference between our study and that of Czyz et al is our utilization of a single device and bone cutting tip with the UBA, which facilitates direct comparison of these tools. Although cross-study comparisons of operative time are challenging given wide variability in anesthesia protocols, surgical techniques, and individual surgeon preferences, the UBA objectively appears to shorten the surgical time when other variables are held constant.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This finding validates earlier research from Czyz et al, who suggested anecdotal improvements in operative time when using a piezosurgical device. 6 One key difference between our study and that of Czyz et al is our utilization of a single device and bone cutting tip with the UBA, which facilitates direct comparison of these tools. Although cross-study comparisons of operative time are challenging given wide variability in anesthesia protocols, surgical techniques, and individual surgeon preferences, the UBA objectively appears to shorten the surgical time when other variables are held constant.…”
Section: Discussionmentioning
confidence: 96%
“…The Sonopet ® UBA is a piezosurgical device that combines torsional and longitudinal oscillation to selectively cut bone and minimize collateral damage to soft tissue. 6,8 As the success of external DCR may correlate with soft tissue preservation and flap management, removing bone without injuring mucosa may potentially improve clinical outcomes (Figure 3). This hypothesis is supported by histopathologic studies in animal models, which have shown that piezoelectric devices result in less direct damage to bony structures and soft tissue compared to traditional drills and oscillating saws.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations